Semiotic Discourse in Contemporary Iraqi plastic Art - Sirwan Rafat Ahmed (Basrah Arts Journal, 2024)
The current research entitled (Semiotic Discourse in Contemporary Iraqi plastic Art) deals with this study, which is based on the semiotic discourse directed by the contemporary Iraqi artist and what is the intended discourse that broadcasts a message that contains social, artistic, religious and other aspects to the recipient through a set of coded symbols and signs that are like codes that need to be decoded by identifying these signs rooted in ancient and contemporary Iraqi culture as well. This study consists of four chapters, the first of which is the methodological framework of the research and includes the research problem, which was summarized by the following question: What is the semiotic discourse in contemporary Iraqi plastic art? As for the importance, it monitored the semiotic discourse and its importance in supporting libraries, then the research objective and its objective, temporal and spatial limits, then defining the terms, and with regard to the second chapter, the theoretical framework that included three topics and indicators, the first is semiotics: its dimensions and concepts, the second is the conceptual discourse, and the third is the semiotic discourse in contemporary plastic art, while the third chapter included society, the sample, the tool, the method, and the method of analyzing sample models, while the fourth chapter included the results, conclusions, recommendations and proposals, and the most prominent results and conclusions are the following: 1- The symbols and signs found in the Iraqi models have their own specificity in the artist's self-expression in terms of their features that indicate what the artist intends in his declared discourse. 2- The Iraqi plastic artist relied on the composition of formal images, organization and contexts that indicate meaning. 3- Iraqi artists share a semiological discourse other than expressing meaning between (technological discourse, the end of the world, the destruction of the earth, religious discourse) in expressing their objective contents. 4- The Iraqi artist was able, through his paintings, to adhere to the rules that determine the relationship between the message and the subject, relying on authentic references that are characterized by objectivity and through which he highlights a semiotic discourse. 5- The Iraqi artistic productions were dominated by the semiological character that provided the opportunity to study them and know their motives and meanings that indicate the discourse directed to the recipient.